2007
DOI: 10.1088/0022-3727/40/20/s20
|View full text |Cite
|
Sign up to set email alerts
|

Surface functionalization and biomedical applications based on SiC

Abstract: The search for materials and systems, capable of operating long term under physiological conditions, has been a strategy for many research groups during the past years. Silicon carbide (SiC) is a material, which can meet the demands due to its high biocompatibility, high inertness to biological tissues and to aggressive environment, and the possibility to make all types of electronic devices.This paper reviews progress in biomedical and biosensor related research on SiC. For example, less biofouling and platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
135
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 50 publications
(66 reference statements)
0
135
1
1
Order By: Relevance
“…The same difference in viability that was observed in the Si crystalline planes also exists with 3C-SiC. (Coletti et al, 2007) have shown the USF 'as grown' 3C-SiC has a contact angle of 52.53°, and (Yakimova et al, 2007) indicates that SiC contains both hydrophilic and hydrophobic sites due to its alternating elemental surface. It should be noted that these substrates are negatively charged, although at a level much lower than the Si substrates.…”
Section: Discussionmentioning
confidence: 59%
“…The same difference in viability that was observed in the Si crystalline planes also exists with 3C-SiC. (Coletti et al, 2007) have shown the USF 'as grown' 3C-SiC has a contact angle of 52.53°, and (Yakimova et al, 2007) indicates that SiC contains both hydrophilic and hydrophobic sites due to its alternating elemental surface. It should be noted that these substrates are negatively charged, although at a level much lower than the Si substrates.…”
Section: Discussionmentioning
confidence: 59%
“…The studies report the significant finding that SiC surfaces are a better substrate for mammalian cell culture than Si in terms of both cell adhesion and proliferation (Coletti et al, 2007). In (bio)-chemical sensor applications, the establishment of a stable organic layer covalently attached to the semiconductor surface is of central importance (Yakimova et al, 2007;Botsoa et al, 2008;Frewin et al, 2009). Recent interest has arisen in employing these materials, tools and technologies for the fabrication of miniature sensors and actuators and their integration with electronic circuits to produce smart devices and systems.…”
Section: Biosensorsmentioning
confidence: 99%
“…We have shown successful binding to ZnO and also SiC surfaces by e.g. APTES, which forms the basis for further attachment of many biomolecules [8][9][10].…”
Section: Introductionmentioning
confidence: 92%